Trade-Based Money Laundering- Impact & Corrective Measures - Salabat, Rizwan (Journal of Pakistan Administration, 2022)
There are three ways to move money for concealing the origins of the proceeds of crime and integrate it with the formal economy; the use of the financial system, bulk cash smuggling and the use of international trade to launder and move the values across borders. In contrast to the other two methods, the scope for abuse of the international trading system is very high but it has attracted little attention. The international trading system has many vulnerabilities that can be exploited by criminals; the enormous and growing volume of trade, involvement of different jurisdictions with their own laws, diversity of finance & trade arrangements, limited resources of Customs authorities whose main focus is not to combat the ML but to collect duties, and pressure from WTO and WCO to eliminate barriers for free flow of trade. This Paper sheds light on the factors that make Pakistan more prone to TBML. This includes the trading practices of its important trading partners. UAE and Hong Kong are transshipment hubs; transshipment makes the origin and ownership of the consignments blurred. Imports from China have been documented to be heavily under-invoiced. Afghanistan has been surviving for decades with a nominal central government with no control over most of the country. Then, some customs clearance practices make Pakistan more vulnerable to TBML. This Paper highlights the enactment of the Antimoney Laundering Act 2010 as an important milestone; this Act defines money laundering and grants sufficient powers to various agencies to investigate predicate offences. The Financial Monitoring Unit is supposed to play the role of the central nervous system for coordination and information sharing. The Directorate of Intelligence & Investigation of Customs is the notified agency to investigate various forms of money laundering including TBML. It has recently detected a few cases of TBML. This Paper concludes that with growing trade volume and peculiar trade, finance and customs practices, TBML remains a serious and compelling threat to Pakistan that can have grave economic, social and political consequences. Pakistan has established a legal and institutional framework that has the capacity to curb and control TBML. In the last part, this paper suggests measures that can increase the capacity and effectiveness of the Pakistani authorities to address the threat of TBML; these include deeper coordination and data sharing among LEAs/institutions, international cooperation, awareness campaigns, training for staff to better identify Pakistan Administration, December 2022 59 TBML techniques and changes in Customs laws and procedures.
Keywords: Trade-Based; Money Laundering; Impact; Corrective Measures